UNA MANERA DIFERENTE DE APRENDER INVESTIGANDO EN LAS ESCUELAS SECUNDARIAS DEL PERU - Espinoza, David Esteban (2019)
The author's experience and their students are centered in the elaboration of 14 experiments related to the study of the electricity; their effects, applications and relationship with the magnetism, trying to learn investigating in the course of physics in way extra scholar. It was largely used recycled materials. So that the demonstrations can be but didactic he/ she decided to manipulate the experiences through the computer, a very simple program was elaborated in BORLAND C++. The team can move easily with its portable handbag when it is required to use in another place. The final work was denominated "Experimental Multiple Demonstrator of Electricity and Magnetism", when being exposed inside the mark of the Scientific Activities Extra scholars at national and international level he/she obtained important prizes. Later on the scholars undertaking an initiative capacity, leadership and trying to continue and to irradiate their experience was organized around the club of sciences "Incubator of School Scientific Investigators" to carry out works of scientific and technological investigation; periodic, waking up the interest to learn investigating of other scholars that will precede them, is advised by teachers and enthusiastic investigators.